PERAN miRNA-21 PENEKAN GEN PTEN PENSIYALAN PI3K/AKT PADA KANKER KOLOREKTAL - Ismail, Ismail; Pulio, Arisanti; Bura, Elvin; Selfiana; Mutmainnah, Nur (Akademi Farmasi Indonesia Yogyakarta, 2022)
Colorectal cancer is one of the leading causes of death in the world caused by various factors such as genetic mutations, epigenetics, dysregulation of communication signaling pathways and gut microbiota. In the presence of genetic, epigenetic mutations, there is a loss of expression and function of PTEN (Phosphatase and TENsin homologues) resulting in continued activation of the PI3K/Akt intracellular signaling cascade involved in colorectal carcinogenesis. The solution to this problem is to use miRNA-21. which plays an important role by suppressing the biological marker PTEN gene that is useful for diagnosis and treatment in colorectal cancer. The aim of this study was to determine the specifi c binding of miRNA-21 with the PTEN gene that plays a role in colorectal cancer based on the AGhybrid and Logistic Probability values. Complete sequences of PTEN genes were obtained from FASTA NCBI and CDS data were obtained from Refseq. Prediction of the binding of mature miRNA-21 with the PTEN gene was carried out using the StarMir Sfold 2.2 website. The predicted results of miRNA-21 binding with 1 target obtained 296 binding models. Specific binding was seen from AGhybrid -23.600 and logistic probability 0.818, there was a binding between PTEN gene binding and miR-21-5p at seedless CDS position 3627-3653 as evidenced by the lowest AGhybrid value of all bindings that occurred.